2010
DOI: 10.1016/j.neuropharm.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

From synapse to nucleus: Novel targets for treating depression

Abstract: The need for newer compounds to treat depression is an ever-growing concern due to the enormous societal and financial ramifications of this disorder. Here, we review some of the candidate systems that could potentially be involved in depression, or an inherent resistance to depression termed resilience, and the numerous protein targets for these systems. A substantial body of literature provides strong evidence that neurotrophic factors, glutamate receptors, hypothalamic feeding peptides, nuclear hormone rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 159 publications
1
54
0
Order By: Relevance
“…In R animals, the decrease in hippocampal BDNF concentrations associated with hippocampal morphological changes is consistent with the depressive phenotype described in humans (Sheline et al, 1999;Bremner et al, 2000;Duman and Monteggia, 2006;Pittenger and Duman, 2008). Animal models of depression and psychosocial stress are associated with reduced hippocampal neurogenesis, hippocampal dendritic arborization, and hippocampal BDNF that are prevented by antidepressant treatment (Watanabe et al, 1992;Magariños et al, 1996Magariños et al, , 2011Sapolsky, 2000;Czeh et al, 2001;Buwalda et al, 2005;Yap et al, 2006;Castrén et al, 2007;Czeh and Lucassen, 2007;Becker et al, 2008;Krishnan and Nestler, 2008;Alleva and Francia, 2009;Covington et al, 2009). Depending on studies, the hippocampal spine density is or not affected by stress events (Chen et al, 2010;Magariños et al, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…In R animals, the decrease in hippocampal BDNF concentrations associated with hippocampal morphological changes is consistent with the depressive phenotype described in humans (Sheline et al, 1999;Bremner et al, 2000;Duman and Monteggia, 2006;Pittenger and Duman, 2008). Animal models of depression and psychosocial stress are associated with reduced hippocampal neurogenesis, hippocampal dendritic arborization, and hippocampal BDNF that are prevented by antidepressant treatment (Watanabe et al, 1992;Magariños et al, 1996Magariños et al, , 2011Sapolsky, 2000;Czeh et al, 2001;Buwalda et al, 2005;Yap et al, 2006;Castrén et al, 2007;Czeh and Lucassen, 2007;Becker et al, 2008;Krishnan and Nestler, 2008;Alleva and Francia, 2009;Covington et al, 2009). Depending on studies, the hippocampal spine density is or not affected by stress events (Chen et al, 2010;Magariños et al, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…Most of the commonly used antidepressant drugs are biogenic amine inhibitors, some rather specific (e.g., citalopram) and others having multiple actions (e.g., venlafaxine). For some time now, there has been interest in developing therapies for depression based on modulation of glutamatergic tone (Covington et al, 2010;Duman, 2014). In particular, a study published by Zarate et al (2006) showed that subanesthetic doses of ketamine, an inhibitor of NMDA (N-methyl-D-aspartate) type ion channels, has a rapid onset of action as measured by decreased scores on the Hamilton Depression Rating Scale in depressed patients deemed treatment resistant.…”
Section: Introductionmentioning
confidence: 99%
“…ERK activity is able to induce phosphorylation of CREB at a specific serine residue, serine133, producing an active transcription complex enabling target gene activation (Conkright et al, 2003), and it is demonstrated that ERK-CREB signal system may play a critical role in the molecular mechanism of depression (Guan et al, 2013). In summary, ERK, CREB and BDNF-mediated signal pathways are indicated to be implicated in the neuroplasticity alterations induced by antidepressants (Covington et al, 2010;Vialou et al, 2013). These previous studies suggest that a CREB-BDNF-ERK circle signal pathway may be involved in the pathogenic mechanism of depression.…”
Section: Discussionmentioning
confidence: 99%